ANALYSIS OF THE CHARACTERISTICS AND PARKING NEEDS OF PARINGIN MARKET, BALANGAN REGENCY - Egga Yosana; Muhammad Arsyad (Universitas Lambung Mangkurat, 2022)
As one of the shopping centers in the Paringin area, Balangan Regency, Paringin market is needed by the community, especially in Balangan Regency. The problem that is often found in areas that have high activity such as markets is parking. One thing that needs to be done to reduce this problem is to analyze the parking area in the area. Things that need to be analyzed are parking characteristics, namely by analyzing parking volume, parking accumulation, parking duration, turnover rate (parking turn over), parking capacity (parking supply), parking index, and parking demand analysis. The purpose of this study is to determine the characteristics of parking and parking requirements in the Paringin market. The method used in this study is a direct survey in the field to obtain the number of parked vehicles, namely by recording the number of vehicles entering and leaving for 3 days according to actual conditions in the field. From the results of this study, it was found that the highest volume was 208 vehicles, the highest accumulation was 50 vehicles and the average parking duration was 2,083 hours/vehicle. The highest turn over value is 0.253 vehicles/SRP/hour, and the highest parking index is 55.68%. The number of parking lots currently available is 103 parking lots so that this capacity is sufficient to accommodate parking users during peak hours.Keywords: parking characteristics, parking demand, paringin market